Control of central air conditioning loads to respond the fault on the HVDC transmission line - Dapeng Wang (The Journal of Engineering, 2019)
The high voltage direct-current (HVDC) transmission is developed rapidly to transmit the clean energy to distant load centres. There will be serious power shortage accidents for the cities if the fault occurs on the HVDC transmission line. Demand response is one of the effective methods to cope with frequency accident. In this study, the control of central air conditioning loads is applied to respond the fault on the HVDC transmission line. The authors focus on the modelling of the central air conditioning loads including the chiller, the inlet and outlet chilled water temperature variation, the heat exchange between chilled water and air, and the space thermal model of the room. When the fault occurs, the chiller will be cut-off immediately. After a period of time, the chiller is turn on to decrease the impact to the users, and the ampere rating of the chiller is restricted to avoid the load shock to the power systems. Simulation results show that the control of central air conditioning loads can respond the accident immediately and the load shock can be avoided in the period of power restoration. Additionally, the users’ comfort is not affected obviously.